POETIC WORDS AS SEMANTIC AND STYLISTIC DOMINANTS IN THE LANGUAGE PICTURE OF THE WORLD OF WRITERS OF PRECARPATHIA - Савчук (Ріжко), Р. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article examined poeticwords as semantic and stylistic dominants, which are very important components of continuum of Precarpathian writers. It determined that these lexical units in the artistic language of Precarpathian authors acquire additional meaning, expanding its semantic potential, become image-symbols.